Phytostabilization of salt accumulated soil using plant and biofertilizers: Field application. (October 2017) - Hong, Sun Hwa; Lee, Eun Young
Abstract: This field study aimed to evaluate the plant growth-promoting potential of biofertilizers. Plant growth-promoting rhizobacterium Arthrobacter scleromae SYE-3 were isolated from local plants grown in saline soil, and isolates were applied as biofertilizers to evaluate growth-promotion effects on lettuce, radish, and Chinese cabbage in cultivated plots (100 m 2 ) of salinized soil. Strain produced 89.15 ± 0.36 mg/L indole-3-acetic acid on day 3 of incubation, and 1-aminocyclopropane-1-carboxylate deaminase activity was 0.20 ± 0.06 OD at the end of the incubation period (after 72 h). After 102 days of cultivation, SYE-3 increased shoot lengths by 23.5%, 48.3%, and 19.5% in experimental lettuce, radish, and Chinese cabbage, respectively, compared with controls. Leaf number increased in lettuce only, by 45.1%. The viable cell count of SYE-3 was maintained during the vegetation restoration period. These results indicate that can serve as a promising microbial inoculant for improving plant growth and therefore enhancing yield in salinized environments, likely through raising plant growth promoting efficiency. Highlights: The biofertilizers consisted of A. scleromae SYE-3 and ion exchange resins. Ion exchange resins capable of removing salts. A. scleromae SYE-3 was salt tolerant and enhancing growth of plant in saline soil. Application of biofertilizers in situ at a field study site in South Korea.